Umbilical Hernia as Forerunner of Primary Umbilical Endometriosis: A Case Report - Saunri Hansadah; Jasmina Begum; Pankaj Kumar; Sweta Singh; Deepthy Balakrishnan; Anirban Kundu (Medeniyet Medical Journal)
Umbilical endometriosis is a type of cutaneous endometriosis that usually follows laparoscopic or surgical procedures that involve the umbilicus. Primary umbilical endometriosis (PUE) is an extremely rare condition and its association with an umbilical hernia is an equally rare condition. To date, only very few cases of PUE with umbilical hernia association have been reported in the medical literature. Report herein is a case of PUE associated with an umbilical hernia who presented with classical umbilical nodule symptoms with cyclical pain and bleeding due to menstruation. The patient underwent omphalectomy with abdominal wall defect repair using prosthetic mesh. The diagnosis was confirmed by histopathological examination of the excised umbilical nodule. This case report highlights a rare entity that should be considered as a differential diagnosis in females of the reproductive age group that presents with the umbilical nodule.